Numerical analysis and experimental verification of time-dependent heat conduction under the action of ultra-short pulse laser - Wang, Yan; Liu, Jingting; Wang, Chunyan; Fan, Xinmin; Liu, Zhaohong; Huang, Xiaodong; Zhang, Lujun; Li, Sensen; Zhang, Yu (Frontiers in Physics, 2024)
Thermal action is a crucial process in laser processing. The classical Fourier heat conduction theory, which assumes an infinite speed of heat propagation, is commonly applied to describe steady-state and mild transient thermal processes. However, under the influence of ultra-short pulse lasers, such as those with picosecond and femtosecond durations, the heat propagation speed within the material is finite and deviates from Fourier's law. This article addresses the unique characteristics of heat conduction in materials subjected to ultra-short pulse laser exposure by integrating Fourier's law with the Gaussian distribution of the actual pulse laser output power density and the material's optical absorption properties. It introduces a time variable to establish a time-dependent heat conduction equation. This equation is numerically analyzed using a difference algorithm. Based on this, simulation and experimental studies on the processing of dental hard tissues with a 1064 nm picosecond laser were conducted. The results show that the experimental processing depths were slightly larger than the simulation results, which may be due to damage to the dental hard tissues and the thermomechanical effects during processing. The results offer a technical reference for adjusting laser parameters in the ultra-short pulse laser processing technique.